Progranulin inhibits autophagy to facilitate intracellular colonization of Helicobacter pylori through the PGRN/mTOR/DCN axis in gastric epithelial cells - Liu, Linlin; Xiang, Miao; Zhou, Jiaqi; Ren, Zongjiao; Shi, Wenjing; Du, Xianhong; Fu, Xiaoyan; Li, Panpan; Wang, Hongyan (Frontiers in Cellular and Infection Microbiology, 2024)
Helicobacter pylori (H. pylori) infection is the primary risk factor for the progress of gastric diseases. The persistent stomach colonization of H. pylori is closely associated with the development of gastritis and malignancies. Although the involvement of progranulin (PGRN) in various cancer types has been well-documented, its functional role and underlying mechanisms in gastric cancer (GC) associated with H. pylori infection remain largely unknown. This report demonstrated that PGRN was up-regulated in GC and associated with poor prognosis, as determined through local and public database analysis. Additionally, H. pylori induced the up-regulation of PGRN in gastric epithelial cells both in vitro and in vivo. Functional studies have shown that PGRN promoted the intracellular colonization of H. pylori. Mechanistically, H. pylori infection induced autophagy, while PGRN inhibited autophagy to promote the intracellular colonization of H. pylori. Furthermore, PGRN suppressed H. pylori-induced autophagy by down-regulating decorin (DCN) through the mTOR pathway. In general, PGRN inhibited autophagy to facilitate intracellular colonization of H. pylori via the PGRN/mTOR/DCN axis. This study provides new insights into the molecular mechanisms underlying the progression of gastric diseases, suggesting PGRN as a potential therapeutic target and prognostic predictor for these disorders.